One health approach: antibiotic resistance among enterococcal isolates in dairy farms in Selangor - Rajendiran, Sakshaleni; Veloo, Yuvaneswary; Abdul Rahman, Salina; Ismail, Rohaida; Zakaria, Zunita; Mansor, Rozaihan; Mohd Ali, Maslina; Khalil, Hassuzana; Syed Abu Thahir, Syahidiah (Multidisciplinary Digital Publishing Institute, 2025)
Background/Objectives: Antibiotic resistance is a growing public health concern. The One Health approach is essential in addressing antibiotic (AR) resistance. Therefore, this study aimed to determine AR among enterococcal isolates in dairy farms across various domains based on the emerging dairy industry. Methods: A total of 208 enterococcal isolates from the workers = 70, milk = 76, and environment = 62 of eight dairy farms in Selangor, Malaysia, were used in this study. The bacterial identification and antibiotic susceptibility testing (AST) were conducted utilising the Vitek-2 system. Results: Approximately 28% of the isolates exhibited susceptibility to all tested antibiotics. A relatively higher proportion of isolates demonstrated resistance to tetracycline, which was followed by erythromycin. The multidrug resistance (MDR) and multiple antibiotic resistance (MAR) index were low in this study. Conclusions: The studied dairy farms exhibited lower AR, MDR, and MAR index values. Nevertheless, ongoing surveillance is essential due to the recent expansion of the dairy farming industry.